Prenatal anesthetic exposure and offspring neurodevelopmental outcomes—A narrative review - Zhou, Nannan; Liang, Shuang; Yue, Xinying; Zou, Wangyuan (Frontiers in Neurology, 2023)
It is common for pregnant women to take anesthesia and surgery, but the effects of prenatal anesthesia exposure on the long-term neurodevelopment of the offspring are unclear. Preclinical animal researches have shown that in-utero anesthetic exposure has neurotoxicity in newborns, mainly characterized by histomorphological changes and altered learning and memory abilities. Regional birth cohort studies based on databases are now the most convenient and popular method of clinical studies. Specialized questionnaires and scales are usually used in these studies for screening and diagnosis of neurodevelopment disorders in offspring. The time intervals between intra-uterine exposure and the onset of developmental outcomes often vary over several years and accommodate a large number of confounding factors, which have an even greater impact on neurodevelopment of the offspring than prenatal anesthesia itself. This narrative review summarized the progress on prenatal anesthetic exposure and neurodevelopmental outcomes in offspring from animal experimental researches and clinical studies, and provided a brief introduction to assess the neurodevelopment in children and potential confounding factors.